Bennett’s Fracture Repair—Which Method Results in the Best Functional Outcome? A Retrospective Cohort Analysis and Systematic Literature Review of Patient-Reported Functional Outcomes - Langridge, Benjamin; Griffin, Michelle; Akhavani, Mo; Butler, Peter E. (Journal of Hand and Microsurgery, 2020)
Surgical fixation of Bennett’s fracture of the thumb is critical to prevent functional impairment; however, there is no consensus on the optimal fixation method. We performed an 11-year retrospective cohort analysis and a systematic literature review to determine long-term patient-reported outcomes following Bennett’s fracture fixation. Retrospective cohort analysis identified 49 patients treated with Kirschner (K)-wire fixation, 85% returned to unrestricted movement during hand therapy. Forty-seven patients (96%) completed the disabilities of the arm, shoulder, and hand (DASH) questionnaires at a mean of 5.55 years from injury, with a mean score of 7.75. Systematic literature review identified 14 studies with a cumulative 541 patients. Fixation included open or percutaneous methods utilizing K-wires, tension band wiring, lag screws, T-Plates, external fixation, and arthroscopic screw fixation. Functional outcomes reported included DASH, quickDASH (qDASH), and visual analogue scores. Superficial wound infection occurred in 4 to 8% of percutaneous K-wire fixation. Open reduction internal fixation (ORIF) methods were associated with a 4 to 20% rate of reintervention and 5 to 28% rate of persistent paresthesia. Closed reduction with percutaneous K-wire fixation should be the first choice surgical method, given excellent, long-term functional outcomes, and low risk of complications. ORIF should be utilized where closed reduction is not achievable; however, the current evidence does not support one method of ORIF above another.
Keywords: Bennett’s fracture; hand surgery; K-wire; functional outcome; long-term